IMPLEMENTASI PEMBELAJARAN PAI DALAM KURIKULUM MERDEKA DI SMP MUHAMMADIYAH 47 SUNGGAL - Maharani Pohan, Siti (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
An independent curriculum is a curriculum that gives schools the freedom to explore their abilities according to the facilities, inputs and resources they have, and gives teachers the freedom to deliver essential and urgent material. And the most important thing is to provide a wide and free space for students to further maximize their potential in order to obtain maximum educational results.This study aims to find out how to effectively implement the Independent Curriculum on PAI subjects. The methodology used in this research is descriptive qualitative with direct observation and actual information from various scientific journals. The results of the study, that the implementation of the independent curriculum in PAI subjects went well because the independent curriculum flow was very compatible with the character of PAI which had to be